Estudio económico sobre alternativas de aplicación de urea para disminuir pérdidas de nitrógeno en el cultivo de maíz (INIAP h-553) zona Quevedo. - Barco Cepeda, Mayra Alejandra (2011)
This research was conducted at the Experimental Station of Tropical Pichilingue National Autonomous Institute for Agricultural Research (INIAP), located in Canton Quevedo Los Ríos province, in 2010. Its main objective was to evaluate the response of different alternatives of urea on performance and development of maize INIAP H-553. Design used a randomized complete block design under a split plot arrangement, with 18 treatments with four replicates and a control in each of the repetitions in which the maize hybrid used INIAP H-553, a distance of planting of 0.80 m between rows and 0.14 m between plants and three nitrogen application rates: 1) 69 kg ha-1, 2) 138 kg ha-1 and 3) 207 kg ha-1, planted in a density of 80000 plants ha-1. In this research some variables such as plant height, percentage of poorly pollinated ears, ear insertion height, N efficiency, percentage of healthy pods, percentage of bad pollinated ears, ear length, ear diameter, number of rows per ear, grain weight per ear, weight of grain yield and gopher. All variables were analysis of variance and means were subjected to the test of Tukey at 5% probability, it was conducted an economic analysis. The interaction of the corn hybrid INIAP H-553 continue found a greater performance the implementation of 207 kg ha-1 nitrogen in the treatment of urea buried with injector 10509.16 kg ha-1. Of all the treatment, greater response to return on maize is reached in the dose 207 kg ha-1 N in treatment (T3) urea buried with injector 10.509,16 kg ha-1, followed by the treatment (T6), urea more vinaza jet (T4) urea more zeolite band, the same as obtain 9.496,05 and 9360,99 kg ha-1of corn. The best treatment of the dose 69 kg ha-1 of N, was more vinaza urea jet (T6) with 8241,47 kg ha-1 , and for the dose 138 y 207 kg ha-1 N urea buried with injector (T3) with and 10509,16 8805,5 kg ha-1, respectively. In recovery of N in the grain, the greater extraction the won the treatment urea more vinaza jet (T6) 207 kg ha-1 N, plus 101.7 kg ha-1, followed by the treatment (T3) buried with injector 138 kg ha-1 N, plus 99,36 kg ha-1 N. The greatest recovery of N in the rest of the plant (without the grain) was the treatment urea more vinaza jet (T5) a 138 kg ha-1 N followed by the treatment witness farmer 138 and 207 kg ha-1 N, plus 88,12 y 74,5 kg ha-1 N, respectively.